Agriculture Inventory Financing (AIF) in Ethiopia: Legal and Operational Overview - Bisrat Mulugeta Zewdu (Mizan law review, 2025)
Agriculture remains the mainstay of the Ethiopian economy, thereby contributing to job creation, forex earnings, food security, poverty reduction and combating climate change. Nevertheless, the sector has not yet realized its potential due to factors including scant access to finance. Lack of collateral is one of the main impeding factors for agricultural lending. This article argues that agricultural inventory financing (AIF) can bridge the collateral gap by facilitating the conversion of agricultural inventories into bankable collateral. In the Ethiopian credit market, Merchandise Loan (ML) is the widely known but the least utilized AIF device. Recent initiatives have introduced Collateral Management Agreement (CMA) and Warehouse Receipt System (WRS), which are gradually expanding in the market despite various limitations and challenges. This article examines the three forms of AIF devices in Ethiopia, highlighting their legal and operational aspects and depicting some of the limitations in their custodial arrangements. A qualitative research approach is used by relying on relevant laws, existing literature and interviews with key stakeholders. The article suggests further legal and institutional analysis, informed by comparative examples, to come up with AIF models that can provide greater flexibility with the collateral custodial arrangement and reduce the cost of financing for the borrowers, while putting in place the right risk mitigation mechanism for the lenders.